Carbon Nanotube Network Ambipolar Field‐Effect Transistors with 108 On/Off Ratio. (19th July 2014) - Derenskyi, Vladimir; Gomulya, Widianta; Rios, Jorge Mario Salazar; Fritsch, Martin; Fröhlich, Nils; Jung, Stefan; Allard, Sybille; Bisri, Satria Zulkarnaen; Gordiichuk, Pavlo; Herrmann, Andreas; Scherf, Ullrich; Loi, Maria Antonietta
<x xml:space="preserve">Abstract</x> Polymer wrapping is a highly effective method of selecting semiconducting carbon nanotubes and dispersing them in solution. Semi‐aligned semiconducting carbon nanotube networks are obtained by blade coating, an effective and scalable process. The field‐effect transistor (FET) performance can be tuned by the choice of wrapping polymer, and the polymer concentration modifies the FET transport characteristics, leading to a record on/off ratio of 108. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>